Here is my approach. Please could you help me check my answer?
[MATH]\because f_x(x,y)=4e^{4x}y^2[/MATH] and [MATH]f_y(x,y)=2e^{4e}y[/MATH]
[MATH]\therefore f(x,y)=e^{4x}y^2+C[/MATH], where [MATH]C[/MATH] is a constant.
Let [MATH]K[/MATH] be a constant s.t. [MATH]f(x,y)=K[/MATH] is the mentioned iso curve.
[MATH]\because[/MATH] the iso curve passes through [MATH](0,2)[/MATH]
[MATH]\therefore f(0,2)=e^{4\times0}(2^2)+C=k[/MATH]
[MATH]\therefore 4+C=k[/MATH]
Recall that the iso curve is [MATH]f(x,y)=k[/MATH],
therefore, [MATH]f(x,y)=k\Rightarrow e^{4x}y^2+C=k\Rightarrow e^{4x}y^2+C=4+C\Rightarrow e^{4x}y^2=4\Rightarrow y=\frac{2}{e^{2x}}[/MATH]
Is [MATH]y=\frac{2}{e^{2x}}[/MATH] the analytical form of [MATH]g(x)[/MATH]?
Many thanks.